تلفیق اور دوسرے فقہی مذہب پر فتویٰ:حدودوضوابط - عبدالکریم عثمان (FIKR-O NAZAR فکر ونظر, 2011)
This paper discusses an important issue of Islamic jurisprudence i.e., talfiq. Talfiq (eclecticism) is a very common methods applied while coping with modern emerging fiqhi issues, however it’s legality has been controversial. This paper attempts to explore the point of view of Hanafi jurists regarding this method and explains the rules, conditions and limits provided by them for the legality of the said concept. Talfiq means “to leave a particular school of jurisprudence without any reason recognized by the Shari‘ah. Taqlid or the strict abiding by the juristic opinions of one particular school, it can be claimed, keeps the Muslims from straying from the straight path, but this does not mean that Shari‘ah itself has made this practice obligatory upon every individual. In view of these two points, a very important question faces the traditional scholars. The question is ‘how to come into terms with contemporary issues faced by Muslim societies or communities where no clear answer has been provided by the jurists of a specific juristic school’? If said, replied that a person is allowed to find a solution in another juristic school, it might be asked as to why taqlid was considered obligatory in the first place. There must, therefore, be some conditions, rules and specific methods governing the practice of looking for solutions to juristic problems outside the school boundaries. This paper critically expounds a few of such rules and conditions.